Intellectual mapping of the sign language role in deaf education: forecasting future reforms - Almos, Rona; Lintangsari, Alies Poetri; Hidayat, Herry Nur (Institute of Advanced Engineering and Science, 2025)
Over the five decades, debatable approaches on deaf education are tangled in the issues of oralism and manualism. The later has valued sign language as the significant factor in the effort of providing quality deaf education. This research aims at mapping the intellectual reports on sign language position in deaf education from 1972 until 2023 including 1,000 documents from Web of Science database. This research use VOS Viewer by implementing co-citation analysis, bibliographic coupling and co-occurrence analysis to see the development of the research, the network and the emerging topical focus. The results suggest that sign language plays the pivotal role in deaf education that predict the future reforms of education for the deaf in form of bilingual education and technology integration. Other significances related to the top discussed themes, the leading authors, the influential publishers are also discussed to seek the interweaving connection among the subemergent research foci.